The Elephants in the Room: Sex, HIV, and LGBT Populations in MENA. Intersectionality in Lebanon; Comment on "Improving the Quality and Quantity of HIV Data in the Middle East and North Africa: Key Challenges and Ways Forward" - Rachel L. Kaplan; Cynthia El Khoury (Kerman University of Medical Sciences, 2017)
In response to this insightful editorial, we wish to provide commentary that seeks to highlight recent successes and illuminate the often unspoken hurdles at the intersections of culture, politics, and taboo. We focus on sexual transmission and draw examples from Lebanon, where the pursuit of data in quality and quantity is teaching us lessons about the way forward and where we are experiencing many of the challenges referenced in the editorial such as discrepancies between national statistics and rates derived via research as well as the impact of protracted political conflict and displacement. Two important points were raised in the editorial about HIV in Middle East and North Africa (MENA) that we would like to expand further: (1) The epidemic is largely driven by drug-related and sexual behavior among key populations; and (2) Several key populations continue to be criminalized and excluded from surveillance programs.